Improving depression-like behaviors caused by diabetes is likely to offer a new perspective for the treatment of non-healing chronic wounds - Dong, Zhiqin; Wu, Jijin; Cao, Hanchen; Lu, Jinqiang (Frontiers in Behavioral Neuroscience, 2024)
Background: Wound healing is a complex process typically involving three stages: inflammatory exudation, cellular proliferation, and tissue remodeling Healing can be impeded by various factors, such as ischemia, sustained pressure, infection, recurrent trauma, or systemic/localized diseases. Chronic wounds are persistent injuries that do not follow the normal healing process and fail to progress through the stages of healing within a reasonable timeframe, like diabetic ulcers, vascular ulcers, pressure sores and infectious wounds.There are various factors that affect chronic wound healing. A large number of research has illuminated that psychological distress may often be related to the wound healing in clinical. Our observations have indicated that the pace of wound healing in diabetic mice is generally slower than that of normal healthy mice, and mice induced by streptozotocin (STZ) and fed with high-fat-diet generally exhibit depression-like behavior. Our experiment delves into the inquiry whether there is an inherent correlation and provide new ideas for clinical treatment to promote wound healing.Methods: This study explored the interrelations among diabetes, depression, and wound healing. Wound healing was assessed using hematoxylin and eosin (HE) staining, Masson's trichrome staining, and immunohistochemistry (IHC) staining for CD31.Then RT-PCR was used to detect the mRNA expression levels of α-SMA, Col1, CD31, and VEGF in wound tissue. Behavioral tests were conducted to evaluate depression.We then regulated specific brain regions through chemogenetic methods, observing the subsequent effects on wound healing.Our findings reveal a connection between the lateral habenula (LHb) region and depression-like behaviors in diabetic models. Inhibiting LHb neuronal activity mitigates these depressive symptoms and enhances wound healing.Refractory wounds can be improved by considering patients' emotional issues from a broad standpoint, which provides fresh concepts for potential clinical treatments in the future.